NURSING PROFESSIONALS IN MATERNAL AND CHILD HEALTH: PERSPECTIVES FROM HAFR AL-BATIN - Awatif Shalan Nuhayr Aldhafeeri, Najla Marzooq Alrashidi, Azizah Abdulrahman B Alshammari, Bashair Awaid Salem Aldhafeeri, Fatimah Fahad Khalaf Aljameeli, Eman Dhamen Sayyah Alshammari,Rahmah Saad Matar Alsulobi. (Chelonian Research Foundation, 2022)
This research paper explores the perspectives and experiences of nursing professionals working in maternal and child health at the Maternity and Children Hospital in Hafr Al-Batin, Saudi Arabia. Through a qualitative approach, the study aims to gain insights into the challenges, opportunities, and best practices in providing quality care to mothers and children in the region. Semi-structured interviews were conducted with six nursing professionals, and thematic analysis was employed to identify key themes. The findings highlight the significance of cultural competence, interprofessional collaboration, and patient-centered care in delivering effective maternal and child health services. The study also reveals the need for continuous professional development and the integration of technology to enhance care delivery. This research contributes to the understanding of nursing professionals' roles and experiences in the context of maternal and child health in Hafr Al-Batin and provides recommendations for improving healthcare services in the region.